The role of academic leadership practices in activating the human capital / A field research of a Iraqi universities sample / Baghdad - الكبيسي, صلاح الدين عواد; الكعود, احمد عبد العزيز (Journal of Economics and Administrative Sciences, 2016)
The aims of this study to diagnose the role of the (relationship and impact) Academic driving practices dimensions (model the way, inspire a shared vision, challenge the process, enable others to act, encourage the heart ) in the activation of human capital (investment and development) for (knowledge, skills, expertise, creative and training capabilities) in a sample of university professors in Baghdad city(Baghdad University, Al Mustansiriya University, University of Technology). (367 )samples were distributed to (232 at the University of Baghdad, 97 at Al-Mustansiriya University and 38 at the University of Technology). The goals of descriptive analytical method research have been used, questionnaire has been a main tool for data collection as well as the interviews and some of the data on sample activities , The research has come to the most important results that is the  presence of a high level of academic driving practices in surveyed Iraqi universities with the superiority of university technology followed by the University of Baghdad and came Al Mustansiriya University was the last, the results also showed a high level of human capital activation(investments and developments) at the University of Technology, and the level of about center at the Universities of Baghdad and Al-Mustansiriya, the most prominent results of the tests was the existence of an extrusive correlation and the positive impact of the of academic leadership practices in activation of  human capital (investments and developments) in Iraqi universities.